Water and Wastewater Services in the Danube Region : Romania Country Note - World Bank (Washington, DC, 2015)
To evaluate and reflect the sustainability of services in the region, an overall sector sustainability assessment was done taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region. Countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess the sector sustainability is included in the Annex of the state of the sector regional report from the Danube Water Program. The outcomes of this assessment for Romania’s water sector are displayed, which also shows average and best practices in the Danube region. The Romanian sector sustainability score is 56, which is below the Danube average sustainability of 64, and which is among the lowest scores in the region. This is partly due to the fact that a large percentage of Romania’s population lives in rural areas, where only 29 percent are connected to pipe water and 10 percent have access to flush toilets (UNECE/WHO 2010). Aside from that, the main deficiencies identified regarding the Romanian water sector through the sector sustainability assessment are affordability, wastewater compliance, and operating cost ratio. Romania is, however, performing well in terms of collection ratio and customer satisfaction. The main sector challenges are: improving access to water and sanitation services in rural areas; strengthening the capacity of operators to ensure implementation of investment projects; addressing affordability issues regarding water and sanitation prices; and improving efficiency of water utilities.